PENINGKATAN KEMAMPUAN LITERASI ANAK USIA DINI DENGAN MEDIA GAME LITERASI - Nita Febrianty; Lisnawati Ruhaena; Lailatum Muthoharoh; Siti Muslichah (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Community service was conducted to assist in improving literacy skills in early childhood students at TK Harapan Gubug through enjoyable methods. The intervention involved the use of literacy games designed using PowerPoint. Interviews were conducted with Group B teachers to assess the outcomes of the intervention. Pre-test and post-test measurements were conducted to evaluate improvements in students' literacy skills. The data collected were analyzed using a Paired Sample T-Test with the aid of JASP software. The results of the intervention showed an increase in children's interest in literacy learning. Moreover, there was a significant improvement in literacy skills, indicated by the average pre-test score of 27.939 and post-test score of 36.515. It can be concluded that the use of literacy games significantly enhances early childhood literacy skills.